Green Synthesis of ZnO Nanoparticles and Its Application in the Degradation of Some Dyes. Issue 6 (5th March 2015) - Davar, Fatemeh; Majedi, Ali; Mirzaei, Alireza; French, R.
<x xml:space="preserve">Abstract</x> A novel ZnO photocatalyst was synthesized by a green method using lemon juice and zinc acetate as precursors, and then the effect of sucrose addition on the initial precursors was investigated. The samples were characterized by field‐emission scanning electron microscopy, X‐ray diffraction, Fourier transform infrared, UV‐visible, and photoluminescence analysis. The result showed that the as‐obtained products with the mix of lemon juice (30 mL) and sucrose had a spherical morphology with the mean particle size of about 21.5 nm. The photocatalytic activity of this sample was tested for the degradation of methyl orange, methyl red and methylene blue solutions. The results also revealed the good photocatalytic activity for the degradation of these three organic dyes. Furthermore, as‐synthesized sample was used in decolorization processes and the treatment of textile dyes (reactive blue 21).